Seven-Ring-Core Erbium-Doped Fiber for OAM-MDM Amplification - Qi Jiang; Xiaobo Xue; Fufei Pang; Liang Zhang; Mengshi Zhu; Heiming Wei; Cheng Du; Wei Li; Tingyun Wang (IEEE Photonics Journal, 2023)
Orbital angular momentum (OAM) mode division multiplexing (MDM) amplification in a seven-ring-core erbium-doped fiber (7-RC-EDF) has been experimentally demonstrated, in which the 1st–4th order OAM modes within each core of the 7-RC-EDF can be supported. By combining the OAM modes with the pump laser into the 7-RC-EDF, 112 OAM modes are predicted to be amplified in the C-band with a net gain of more than 22.36 dB with the differential modal gain (DMG) of less than 1.7 dB. The optical signal-to-noise ratio (OSNR) can be higher than 30 dB. As a proof of concept, signals with three wavelengths were individually converted into the 2nd–4th higher order OAM modes, respectively, and then injected together into one ring core of the 7-RC-EDF. The amplification with a net gain of more than 27.7 dB and OSNR of more than 22 dB was achieved. The proposed wavelength division multiplexing (WDM) combined with the OAM-MDM technique verified its potential applications in large-capacity OAM-MDM optical fiber communication systems.